Political intervention, corporate governance, earnings management, and firm performance among Malaysian firms / Nurul Azlin Azmi - Azmi, Nurul Azlin (2021)
The management discretionary practices and loosen of accounting standards provide mask opportunities for earnings management. Highly manage earnings results in low earnings quality and leads to wrong decision making for financial reporting users. The doubtful of board quality has been worsen with the appearance of political intervention as this subsequently erode public confidence towards the firm’s earnings quality. The purpose of this study is to examine the effect of political intervention and corporate governance mechanisms on earnings management and firm performance in Malaysia. Prior studies on Malaysia's political intervention are scarce, and the results are inconclusive toward earnings management and firm performance. The surge of political intervention create agency problem in which it can influence the director’s independence and divert the firm’s primary objective to a politician’s motive. Furthermore, the Malaysian Code on Corporate Governance 2021 (MCCG 2021) discouraged listed firms from appointing an active politician as a director on its board. Firms are considered directly politically connected if one of the directors is a member of parliament, a minister, head of state, or closely related with a top officer or party, or government officer. Meanwhile, the indirect political connection comes from the close bond ties, such as family ties of the politician or royal family. The sample of this study is based on 3,120 firm-year during the 2013 – 2017 periods. This study employs a static panel analysis with both firm and year fixed effects. The study retrieved the political intervention and corporate governance variables from the downloaded annual report, whilst the remaining data were collected from the Data stream. This study finds that political intervention has positive and significant relationship with earnings management – Accrual and Real. Meanwhile, political intervention is negative and significant on market-based performance (Tobin’s Q); but positively significant on accounting-based performance – ROA & ROE. This suggests that the impact of political intervention could outweigh the benefits from corporate governance changes. Then, good quality of boardroom has a positively significant on firm performance and suggesting increase in internal monitoring as Tobin’s Q increases. Ownership structures and external audit also have significant effect on earnings management and firm performance. The findings of the study generally reveal the effect of political intervention on earnings management and it is the right time for the regulator to limit the politician's involvement to curtail earnings management practices in the firms. This study adds to the growing of the literature by applying Resources Dependency Theory and Social Network Theory to explain how the close bond ties consider as indirect political intervention.